A systematic review of suicide and suicide attempts in adolescents with psychotic disorders - Barbeito, Sara; Vega, Patricia; Sánchez-Gutiérrez, Teresa; Becerra-García, Juan Antonio; González-Pinto, Ana; Calvo, Ana (Elsevier B.V., 2022)
Background: Suicide is the main cause of premature death in patients with psychosis. Therefore, the goal of the present study was to review suicide in adolescents with psychotic disorders by evaluating factors associated with suicidal acts. Ours is the first systematic review of suicide in this population. Method: We performed a systematic review of suicide in adolescents (10 to 19 years) with psychotic disorder. Results: We identified 10 studies, only 2 of which were randomized clinical trials. The results revealed high rates of suicidal behaviour in this population: the times of higher risk were the time before admission and the period immediately following discharge. The factors most associated with suicide attempts were depression, distress with psychotic symptoms, fewer negative symptoms at baseline, positive symptoms, and anxiety disorders. Associated factors included previous psychiatric history or psychiatric admissions, female sex, prior suicidal behaviour, family history of completed suicide, and nicotine dependence. Limitations: Clinical and methodological diversity of the studies. Conclusions: Adolescents with psychotic disorders had a major risk of suicidal behaviour, and specific factors were associated with the act. Early detection of adolescents with psychosis is vital, since it has been found that early intervention can prevent suicidal acts in young people. However, it is necessary to perform more studies, particularly randomized controlled trials, on suicide and suicide attempts, particularly in adolescents.
Keywords: adolescents; early onset of psychosis; psychotic episode; suicide; suicide attempt; suicide profile; Scopus; JCR